Productivity improvement using SMED concept and industrial engineering (IE) tools in reducing CNC machine set up time - 445053 Ong, Teong Khuan (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Industri)) - Universiti Teknologi Malaysia, 2006